Neuroprotective Effects of Fingolimod Supplement on the Retina and Optic Nerve in the Mouse Model of Experimental Autoimmune Encephalomyelitis - Yang, Tao; Zha, Zheng; Yang, Xiao; Kang, YueZhi; Wang, Xin; Tong, Yanping; Zhao, XueSong; Wang, Lei; Fan, YongPing (Frontiers in Neuroscience, 2021)
Fingolimod, a structural analog of sphingosine 1- phosphate (S1P) receptor modular agent, is the first oral therapy approved for the treatment of relapsing-remitting MS. Although the immunomodulatory and neuroprotective properties of fingolimod have been reported, its impact on the visual system, which is often affected by MS, is unknown. Herein, we evaluate the therapeutic effects of fingolimod on the visual system in EAE mice. We showed that a reduction of demyelination and axon loss in the optic nerve as well as cellular infiltration, especially in the recruited macrophages in the optic nerve and retina. Under fingolimod administration, retinal macroglia including astrocytes and Müller cells were diminished and astrocytes in the optic nerve were also decreased in the EAE mice. The microglia were hyperactivated in the retina and optic nerve in the EAE mice compared to controls, which could, however, be alleviated by fingolimod treatment. Moreover, apoptosis of retinal DRG and oligodendrocytes in the optic nerve was significantly reduced with fingolimod treatment compared to the untreated EAE mice. These results suggest that fingolimod exerts neuroprotective and anti-inflammatory effects on the retina and optic nerve in a mouse model of EAE. Given that the visual system is a vulnerable target in MS patients, fingolimod as an immunomodulatory agent might be a potentially useful therapeutic agent that warrants further neuro-ophthalmological investigation.